Carcinoma Thyroid : A Literature Review - Hayaza, Safira Said; Wahyudi, Belynda Rahmalia Sanceska; Triani, Eva (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Thyroid carcinoma is a type of cancer that originates from the cells of the thyroid gland, and its incidence has been steadily increasing in the last decade. It is the 7th most common type of malignancy among women, after ovarian carcinoma, with nearly 80% of diagnosed cases being the papillary type. Triggering factors that contribute to the development of thyroid carcinoma include genetic influences, iodine deficiency, history of overexposure to radiation, and history of goiter. Various clinical guidelines have been developed for the diagnosis, therapy and follow-up of differentiated thyroid carcinoma (DTC). This article aims to analyze the risk factors, clinical characteristics, and different treatment approaches for thyroid carcinoma, as well as explore new factors contributing to the increasing incidence of this disease. By doing so, the reader is expected to gain a deeper understanding of thyroid carcinoma. This article discusses important aspects such as epidemiology, etiology, pathogenesis, clinical manifestations, diagnosis, and prevention related to thyroid carcinoma, so that the selection of management can be made more appropriately, and help reduce the rate of increase in the incidence of this disease.